Experimental Archaeology at the University of Bologna, widening and opening archaeological research - Maurizio Cattani (Groma, 2016)
The establishment of an Experimental Archaeology Laboratory at the University of Bologna has created the opportunity to offer students new training methods and to take on scientific research dedicated to the analysis and comprehension of ancient technologies. The Laboratory is based on the participation of several specialists, including archaeologists, technicians, ethno-archaeologists, and experts in archeometry, with the shared aim of investigating, documenting and understanding the past. Using limited financial resources, initial activities took place near the Bronze Age settlement of Solarolo, where the synergy among local institutions, land owners, academics and the general public created a basis on which to prepare activities and zones dedicated to different aspects of experimental archaeology.